The Implementation of Primary Teacher’s Forum and Its Impact Based on Teacher’s Perceptions - Sukarjita, I Wayan; Astiti, Kadek Ayu (Jurnal Pendidikan Progresif, 2019)
The Implementation of Primary Teacher’s Forum and Its Impact Based on Teacher’s Perception. Objectives: This study aims to find out the implementation profile of primary teacher’s forum in East Sumba, Indonesia which consisted of the existence, organization, management, and its impact based on teacher’s perception. Method: This study is a quantitative descriptive study using a combination research method. Data were collected using questionnaires and interviews. The sampling technique used in this study was cluster sampling, which consisted of 748 primary teachers. Findings: Teacher’s forum in East Sumba has been formed at about 10 years and workplan has been arranged before. The activities always hold in every semester. Directly monitoring is always done by supervisor in every meeting. Conclusions: Teacher’s forum in East Sumba has been work properly and give significantto improve teacher profesionalism.Keywords: Primary teacher’s forum, teacher profesionalism, Indonesia DOI: http://dx.doi.org/10.23960/jpp.v9.i1.201909